Factor influencing student's intention to be entrepreneur: an evidence from Indonesia higher education / Harif Amali Rivai - Rivai, Harif Amali (Malaysian Academy of SME & Entrepreneurship Development (MASMED), 2012)
The current study examines factors influencing student's intention to be entrepreneur. These factors include perceived educational support, perceived relational support, perceived structural support, self-confidence and organizational culture. The data were drawn from 342 university students in West Sumatera Province, Indonesia who registered in Department of Business or Management from private and public universities. The results of structural equation modeling (SEM) supported that the theoretical model met goodness-of-fit criteria. The findings concluded that there is significant relationship between all three perceived educational support, perceived relational support, perceived structural support, and entrepreneurial intention which mediated by self-confidence. Meanwhile, organization culture in the universities did not significantly influence student's intention. Implication, limitation and suggestion for future research are discussed.